EFEKTIVITAS LAYANAN KONSELING KELOMPOK DENGAN PENDEKATAN RATIONAL EMOTIVE BEHAVIOR THERAPY MENGGUNAKAN TEKNIK SIMBOLIS DAN LIVE MODELING DALAM MEMINIMALISIR KECEMASAN KARIR MAHASISWA AKHIR - Nurhikmah M.; Siti Dea Ananda (Didaktika : Jurnal Kependidikan, 2022)
This study aims to determine the effectiveness of group counseling services with the Rational Emotive Behavior Therapy approach using symbol modeling and live modeling techniques in lowering the careers of final students. The participants in this study were 7 postgraduate students at UIN Sunan Kalijaga Yogyakarta. This research is an experimental study using a single group pretest-posttest design that only uses one group of subjects (single case) and performs measurements before and before giving treatment to the subject (pretest-posttest) using the instrument, namely the final student career anxiety scale that has met the standard. the required validity and reliability. Experiments were carried out using group counseling with an approach using Rational Emotive Behavior Therapy, symbolic modeling techniques and live modeling. Method of data analysis with paired T test. The results of data analysis showed the value of t = 8.908 with p = 0.000 0.05 which means that there is a significant difference in the level of career anxiety of final students before and before receiving treatment for group counseling services using the Rational Emotive Behavior Therapy approach with live modeling and symbolic modeling techniques, and proven to be effective in reducing the level of career anxiety of final students.Keywords: Group Counseling Services, REBT, Symbolic Modeling, Live Modeling, Final Student Career Anxiety